2018
DOI: 10.1093/ndt/gfy225
|View full text |Cite
|
Sign up to set email alerts
|

Failure of first meningococcal vaccination in patients with atypical haemolytic uraemic syndrome treated with eculizumab

Abstract: Immunogenicity of first quadrivalent meninongococcal vaccination is insufficient in patients with aHUS. Booster response is promising, but incomplete. Therefore, establishing antibiotic prophylaxes seems pivotal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Interestingly, a question arises for the terminal pathway deficiencies: if the pathogenic strain is serum-sensitive, will the vaccine work if the response depends on C5b-9 formation only? The answer is most likely not, since the C5 is inactive; thus, the response will depend on the Fc-mediated phagocytosis (Jodele et al, 2016;Reher et al, 2018;Gäckler et al, 2020).…”
Section: E Therapeutic Approach To Treat Complementmentioning
confidence: 99%
“…Interestingly, a question arises for the terminal pathway deficiencies: if the pathogenic strain is serum-sensitive, will the vaccine work if the response depends on C5b-9 formation only? The answer is most likely not, since the C5 is inactive; thus, the response will depend on the Fc-mediated phagocytosis (Jodele et al, 2016;Reher et al, 2018;Gäckler et al, 2020).…”
Section: E Therapeutic Approach To Treat Complementmentioning
confidence: 99%
“…Antibiotic prophylaxis should be administered in all patients with non-protective or unknown antibody titers against MenB analogous to the procedure after vaccination with the quadrivalent conjugate vaccine against serogroups A, C, W, and Y [19]. There is controversy about the sense of elimination of Neisseria sp.…”
Section: Protective Titers 50%mentioning
confidence: 99%
“…Previous studies have reported general reduced immunogenicity to vaccinations in patients with end-stage renal disease and kidney transplant recipients [17,18]. Immunogenicity of one vaccination with quadrivalent meningococcal polysaccharide conjugate vaccine was insufficient in patients with aHUS [19]. Due to the use of human complement in the bactericidal assay it is currently not possible to analyze serum from patients with ongoing eculizumab treatment, because the complement cascade is blocked by eculizumab [20].…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients need to be vaccinated against Neisseria meningitides serogroups A, C, W, Y and B prior to therapy initiation or, alternatively, prophylactically treated with antibiotics until 2 weeks after the vaccination. Notably, failure of the first vaccination to provide sufficient immunization has been reported and therefore antibiotic prophylaxis seems pivotal, as fatal infections with the germ have been reported even after vaccination [20, 21].…”
Section: Treatment Of Ctmamentioning
confidence: 99%